Landing technique is related to patellar tendon loading during a volleyball block jump movement - Janssen, I.; Steele, J. R.; Brown, N. A. T. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Patellar tendinopathy is the most common overuse injury incurred in volleyball. Although high patellar tendon loading is thought to be a causative factor of patellar tendinopathy, it remains unknown how landing technique is related to high patellar tendon loading. Landing kinematics and patellar tendon loading were quantified for 49 volleyball players who performed a lateral stop-jump block movement. Correlations identified that volleyball players who displayed high ankle dorsiflexion velocity, high ankle dorsiflexion acceleration, and high knee flexion acceleration also generated greater peak patellar tendon force and faster patellar tendon force development. These results suggest that athletes who demonstrate rapid ankle and knee flexion when landing may be predisposed to developing patellar tendinopathy.